Strategi Kepala Madrasah Tsanawiyah Plus Nabawi Kedungadem Bojonegoro dalam Mengembangkan Lembaga Pendidikan Islam - Sirojudin, Didin; Alamsah, Bayu (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
The principal's strategy in developing educational institutions at Madrasah Tsanawiyah (MTs) Plus Nabawi Kedungadem Bojonegoro is a qualitative research. Data analysis is the process of systematically searching for and compiling data from interviews, observations and documentation by organizing the data and choosing which ones are important and which ones need to be studied and drawing conclusions so that they are easy to understand. The results of the study found that madrasas had carried out their maximum efforts in an effort to develop educational institutions at MTs Plus Nabawi Kedungadem Bojonegoro. The strategy of the head of MTs Plus Nabawi Kedungadem Bojonegoro consists of two strategies, namely First, improving the quality of Human Resources, this program focuses on improving the quality of teachers in teaching students. This program focuses on increasing the potential of students by creating four programs that are directly related to madrasas and the community. These programs are in the form of: the tahfidz program, collaboration with Religious Development (Field) Institutions, Sports and Arabic Language Development, commemoration of Islamic holidays (PHBI), and the Smart Education Center (SEC). Second, in the form of improving the quality of education through special programs at MTs. This program is in the form of coaching and sending teachers and staff to seminars, workshops and coaching from the head of the madrasah himself.